The Role of the Principal as a Supervisor in Enhancing Teachers’ Pedagogical Competence at SD Negeri 1 Pamotan, Rembang - Nurun Nikmah; Titik Haryati; Sumarno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the role of the school principal as an academic supervisor in enhancing teachers’ pedagogical competence at SD Negeri 1 Pamotan, Rembang. Pedagogical competence, as mandated by Law No. 14 of 2005 on Teachers and Lecturers, is a critical component in managing the learning process and fostering meaningful classroom experiences. A qualitative case study approach was employed, with data collected through in-depth interviews with key school stakeholders, classroom observations, and document analysis. Thematic analysis was used to explore the principal’s supervisory practices and their influence on teacher development. The findings reveal that the principal implemented a structured and collaborative supervision process, encompassing planning, implementation, follow-up, and evaluation stages. However, the integration of educational technology and innovative teaching strategies was found to be limited, thereby reducing the overall effectiveness of the supervision in improving student learning outcomes. This study contributes to the existing body of literature by underscoring the strategic role of principals in strengthening pedagogical competence through academic supervision that embraces technology and innovation. It also highlights the importance of ongoing professional development and systematic feedback in enhancing teacher quality and instructional effectiveness.